(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
High ambient temperature in tropical, especially during the daytime of Garut lamb cause high level of stress and low productivity. To overcome it can be improved the management. If the feed is given in the evening, its metabolism process will take place throughout the night with the lower temperature. This method is expected result the higher productivity include the meat quality. So the aim of this study was to evaluate the influence of feeding time (morning and evening) toward the physical meat characteristics of Garut lamb. 12 Garut lamb were used. They were placed in 12 individual cages. This study used block randomized design. As treatment was feeding time. As feed was a mix of field grass and concentrates (40:60). Data of physical meat characteristics were analyzed by t-test. The physical meat characteristics include value of pH, the ability to water bind, cooking loss, and score of meat colour were not significant. Garut lamb that was given feed at morning time, significant resulted the meat with more tender (1.04 kg/cm2) than the feeding time at evening (1.59 kg/cm2) (P<0.05). It can be concluded that the physical meat characteristics (except meat tenderness) of Garut lamb were similar in both different feeding time. The treatment of different feeding time can be change the behaviour of Garut lamb.